Evaluated efficiency of Trichoderma viridi and Sewak (Arak) Powder to Control The Root Rot Fungi of Pistacia khinjik Seedlings - Noori Alkhero, Anwar (Journal of Kerbala for Agricultural Sciences, 2017)
The current study showed the effect of Trichoderma viridi on growth inhibition of Pistasia khinjik seedling root rot fungi which usually used in biological control with pathogens and using four concentrations of sewak powder 0 , 10 , 20 , 30 gm/l represented control treatment . Isolation results showed that the four fungi Fusarium chlamydosporium had 50% in frequency ratio then the fungus Rhizoctonia solani and Macrophomina phaseiolina had 16.6% then Fusarium culmorum which had 8.3 % . The results of biological control of tested fungi by Trichoderma viridi showed that all fungi were affected by biological resistance in different degrees , the degrees of inhibition was the first and second degree so those two degrees make the fungi with high parasitic abilities against pistasio root rot fungi . The results of bioassay of sewak powder in several concentrations showed that incorporeal differences in the efficiency of sewak powder effect on root rot fungi control as compared with biological control for the same fungi where the fungi affected in different ratios, F. chlamidosporum inhibited aconcentration 10gm/l of sewak powder which was maximum inhibition ratio 77% , Rhizoctonia solani , F. culmorum , M. phaseolina showed inhibition ratios 72 , 49 , 28 % respectively , Rhizoctonia solani showed a height ratio at two concentrations 20 and 30 gm / l , inhibition ratio were 40 and 55 % , while the other fungi had no effect even with high concentrations of sewak powder . R. solani was more fungi affected with concentration stepped comparative with others fun